Partie de l'Amérique septent? qui comprend la Nouvelle France ou le Canada - Robert de Vaugondy, Gilles, 1688-1766 ([Paris?], 1755)
Hand coloured. Decorative title cartouche. Relief shown pictorially. Bar scales in "milles pas géométriques" and nautical leagues. "C. Haussard, Sculp." (to the bottom left of title cartouche on main map). Inset: Supplement pour les lacs du Canada. CNS map no. 402.